Effect of preparation method on performance of Cu–Fe/SiO2 catalysts for higher alcohols synthesis from syngas. Issue 60 (8th June 2016) - Sun, Chao; Mao, Dongsen; Han, Lupeng; Yu, Jun
Abstract : Cu–Fe/SiO2 catalyst prepared by ultrasound-assisted impregnation exhibits higher CO conversion and alcohols yield than those by the other methods. Abstract : Five Cu–Fe/SiO2 catalysts were prepared by deposition–precipitation, solid state impregnation, solid-state chemical reaction, citric acid combustion, and ultrasound-assisted wet impregnation, and their physicochemical and catalytic properties for higher alcohols synthesis were investigated. The results showed that the Cu–Fe/SiO2 catalyst prepared by ultrasound-assisted impregnation had a higher dispersion and reducibility of active metal oxides, and the largest S Cu, which increased the amount of adsorbed CO and the ability for CO dissociation. As a result, the CO conversion and space time yield of total alcohols of the catalyst reached 14.04% and 104.3 g kg −1 h −1, respectively, which were better than the other catalysts.